Limosilactobacillus reuteri DSM 17938 reverses gut metabolic dysfunction induced by Western diet in adult rats - Abuqwider, Jumana; Di Porzio, Angela; Barrella, Valentina; Gatto, Cristina; Sequino, Giuseppina; De Filippis, Francesca; Crescenzo, Raffaella; Spagnuolo, Maria Stefania; Cigliano, Luisa; Mauriello, Gianluigi; Iossa, Susanna; Mazzoli, Arianna (Frontiers in Nutrition, 2023)
Introduction: Microencapsulation of probiotic bacteria is an efficient and innovative new technique aimed to preserve the bacterial survival in the hostile conditions of the gastrointestinal tract. However, it is of fundamental importance to understand whether the microcapsule preserve the effectiveness of the bacterium contained within it.Methods: male Wistar rats of 90 days were fed a control diet or a Western diet for 8 weeks, with rats fed the Western diet divided in three groups, one receiving the diet only (W), the second group receiving the Western diet and free L. reuteri DSM 17938 (WR), the third group receiving the Western diet and microencapsulated L. reuteri DSM 17938 (WRM). Gut microbiota composition after 8 weeks of treatment has been evaluated, together with occludin, one of the tight junction proteins, in ileum and colon. Markers of inflammation were also quantified in portal plasma, ileum, and colon, as well as gut redox homeostasis.Intestinal microbiota was negatively influenced by the Western diet, with no significant effect elicited by supplementation with free and microencapsulated L. reuteri. However, L. reuteri, in both forms, was effective in preserving the integrity of the intestinal barrier, thus protecting enterocytes from the development of inflammation and oxidative stress.From these whole data, it emerges that L. reuteri DSM 17938 can be an effective probiotic in preventing the unhealthy consequences of the Western diet, especially in the gut, and that microencapsulation preserves the probiotic effects, thus opening to the formulation of new preparations able to improve gut function independent of the dietary habits.